Isolation and Characterization of Antitumor Alkaloid from Poppy Capsules (Papaver somniferum). (13th September 2012) - Bulduk, Ibrahim; Taktak, Fulya
Abstract : Noscapine, a phthalideisoquinoline alkaloid derived from opium, has been used in the treatment of various cancer types. Its low-toxicity profile has increased attention to this alkaloid. With regard to increasing demand for this compound, we developed a new method for isolation of noscapine from dried capsules of Papaver somniferum . Noscapine was successfully isolated from poppy capsules for the first time and the purity of the isolated compound was determined to be over 99.59% by HPLC analysis. The structure of noscapine was confirmed by H 1 NMR, C 13 NMR, FT-IR, elemental analysis, and HR-ESI-MS methods.